Methodology for Scale-Resolving Simulation of Unsteady Effects in Turbomachines - Duben, Alexey P.; Sapozhnikov, Viacheslav A. (Supercomputing Frontiers and Innovations, 2025)
Methodology for studying effects associated with periodic unsteady impact of neighbouring rows in turbomachines is presented. The two-stage procedure of an investigation is as follows: simulation using an approach based on solving the Reynolds-averaged Navier–Stokes equations (RANS) of an entire turbomachine at the first stage and scale-resolving simulation (SRS) of a particular row at the second. The methodology exploits the following methods and technologies, which are implemented in the NOISEtte computational algorithm: the nonlinear harmonics method as a RANS approach to obtain unsteady inflow parameters for SRS; the hybrid Improved Delayed Detached Eddy Simulation approach for SRS of the row under detailed study. SRS considers using the dynamic synthetic turbulence generator in a form of volumetric source terms (VSTG) to reproduce unsteady periodic turbulent perturbations. A dynamic version of the VSTG, the parameters of which depend on the flow upstream the source region, is formulated. Details of the parallel heterogeneous implementation of the dynamic VSTG are discussed. To demonstrate the applicability of the presented methodology, a simulation of non-stationary effects in a cascade of T106 low-pressure turbine blades was performed.